2017
DOI: 10.1021/acs.energyfuels.7b02626
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Aromatic Clusters of Different Coals Based on Benzene Carboxylic Acids from Coal via Oxidation

Abstract: Benzene carboxylic acids (BCAs) are considered to be an important group of chemicals and widely used in the chemical industry. The generation of BCAs from coal via oxidation is widely studied, indicating that the distributions of BCAs are various with different coals and the yields of BCAs with lower numbers of carboxyl groups increase in the process of coalification. However, the relationship between distributions of BCAs and the aromatic clusters of coal is unclear. In this work, combined with the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…However, the 13 C CP/MAS spectra indicated that the organic structure of biomass and coal is different. Anthracite contains a great amount of hydrogenated polycyclic aromatic rings arranged in a linear catenation order, whereas biomass samples are rich in polysaccharides, proteins, lipids and other abundant compounds [82,83]. The high moisture content in original woodchips and olive stones could also have a strong impact on the calorific value of torrefied biomass briquette, confirming the previous results of Demirbas [84].…”
Section: Discussionsupporting
confidence: 84%
“…However, the 13 C CP/MAS spectra indicated that the organic structure of biomass and coal is different. Anthracite contains a great amount of hydrogenated polycyclic aromatic rings arranged in a linear catenation order, whereas biomass samples are rich in polysaccharides, proteins, lipids and other abundant compounds [82,83]. The high moisture content in original woodchips and olive stones could also have a strong impact on the calorific value of torrefied biomass briquette, confirming the previous results of Demirbas [84].…”
Section: Discussionsupporting
confidence: 84%
“…The parallelogram-shaped aromatic fragments are not the actual structure of aromatic units in coal but only a method to enrich the structural diversity of coal. 22 The linear and circular catenations were also proposed by Solum et al 56 and exploited in the models by Yang et al 57 Previous studies indicated that certain polycyclic aromatic hydrocarbons in coal affected by igneous intrusions, such as fluoranthene and benzofluoranthene, contained a certain number of pentagonal aromatic rings, 58 which may be caused by tectonic stress 59,60 or high temperature. 61 Considering that the three thermally altered coals in this study were affected by igneous rock intrusions, the pentagonal aromatic rings were incorporated into the aromatic units of thermally altered coals by removing a protonated aromatic carbon from the outside hexagonal aromatic ring and creating an aromatic carbon− carbon covalent bond for aromatic ring closure.…”
Section: Resultsmentioning
confidence: 89%
“…The parallelogram-shaped aromatic fragments are not the actual structure of aromatic units in coal but only a method to enrich the structural diversity of coal . The linear and circular catenations were also proposed by Solum et al and exploited in the models by Yang et al…”
Section: Resultsmentioning
confidence: 99%
“…The χ b value of raw coal samples increased with an increase of coal rank (from lignite to bituminous coal. 18) And the χ b value of raw biomass is the lowest.…”
Section: Evaluation Of Mean Aromatic Cluster Size Viamentioning
confidence: 98%